Bisexual differences with reference to finger-ball dermatoglyphics among Jaunsari tribe of Uttarakhand - Pathan, Farzana; Mondal, P R (Journal of Indian Academy of Forensic Medicine, 2020)
The scientific study of finger ball ridges is called finger-ball dermatoglyphics, which is associated with human genetics, specifically with chromosomal abnormalities and forensic science. Features of finger-ball prints are used in anthropological applications, and it has a great significance in human variation. In the present study, the bilateral finger-ball prints were collected randomly from 170 individuals of Jaunsari Tribe (males = 70 and females = 100) from Jaunsar – Bawar of Dehradun District in Uttarakhand. The analyses were done by the method propounded by Cummins and Midlo (1943). The pattern types, Total Finger Ridge Count (TFRC) and Absolute Finger Ridge Count (AFRC) were calculated and analyzed. The test of Significance i.e. χ2 - test and t-test, was also done. The Furuhata’s Index (Whorl/loop index) was greater among males (78.94) as compared to the females (70.78). The value of Dankmiejer’s (Arch/Whorl) Index was higher among females (15.12) than males (6.66). This can be attributed to a higher frequency of whorl among females. Pattern Intensity Index is almost equal, and the value for males was 14 and for female was 13.31.